LEGAL ASPECTS OF LAND PROTECTION IN THE PROCESS OF OVERUSE - Мачуська, Ірина; Гуляр, Тетяна; Аргатюк, Ірина (SWorldJournal, 2025)
The article examines the features of land protection in the process of subsoil use. It is noted that mineral extraction is a process that is closely related to the negative impact on land resources.It is proven that the need to apply measures to protect